Impact analysis of energy-efficient demand-side management in six-bus systems: replacing lighting loads based on consumer preferences - Rashid, Muhammad Mahbubur; Hossain, Tasfia; Barua, Dhrupadi; Datta, Mohima; Islam, Rashedul; Alazmi, Ahmad Mmzr (AlamBiblio Publishers, 2025)
One of the most important strategies for improving power utilization and lowering total energy usage in distribution systems is energy-efficient Demand Side Management (DSM). Within a substation's load profile, this study assesses the effects of swapping out incandescent lights for consumer-preferred, energy efficient substitutes like LEDs and Compact Fluorescent Lamps (CFLs). Despite certain harmonic distortion issues related to non-linear lighting loads like CFLs, DSM techniques in particular, demand response strategies have been demonstrated to lower power costs, improve power factor, but increase Total Harmonic Distortion (THD). The study evaluates system metrics, including power, THD, power factor, and energy consumption, under different load combinations using MATLAB simulations. The findings of analyzing optimal power flow (OPF) on a six-bus network and modeling a balanced three-phase system show decreases in real power demand, operational losses, and system expenses. Additionally, the economic advantages of DSM interventions are highlighted by differences in Locational Marginal Pricing (LMP) among bus nodes. Results indicate that DSM techniques greatly improve system sustainability and efficiency in power distribution networks by implementing targeted load reduction and energy-efficient lighting